Serologic status at 10 months of infants born to hepatitis B positive mothers given prophylaxis - A prospective cohort study - Saradakutty, Geetha; Dharmarajan, C; Kumar, A Santhosh (Indian Journal of Child Health, 2017)
Rationale: Perinatal exposure is the most common mode of transmission of hepatitis B (HB) infection in neonates. Prevention of perinatal transmission of HB is important to decrease overall carrier state. Objectives: To estimate the rate of HB carrier status among children born to HB surface antigen (HBsAg) positive mothers at 10 months of age measured by HBsAg status and to assess the efficacy of prophylaxis (HB vaccine [HBV] and HB immunoglobulin [HBIG] administration) as measured by the anti-HBs titer at 10th month of age. Methodology: This was a hospital based prospective cohort study of infants born to HBsAg positive motherbetween April 2008 and October 2008 with a follow-up at 6 weeks, 14 weeks, and 10 months of age. After informed consent from the parents, 0.5 ml of recombinant vaccine was given to all. HBIG was given to only those who could afford to buy it. At 6 and 14 weeks of age, 0.5 ml of recombinant vaccine was given according to the IAP immunization schedule along with other UIP vaccines to all neonates. At 10 months of age (plus 1 week), 69 infants completed 3 doses of HBV. Anti-HBs titer and HBsAg status were measured. Anti-HBs titer >100 IU/L was taken as a good responder. Results: Total 125 infants were initially recruited. Allwere vaccinated with HBV within 12 h of birth. HBIG was given to 96 infants (76.8%) and only 69 (55.2%) completed 3rd visit. Carrier state in infants born to HBsAg positive mothers at 10 months of age was 1/69 (1.44%). 43/69 (62.35%) had good antibody response out of which, 41 were given both HBV and HBIG. In those given only vaccine, 2/7 (28.55%) had good antibody response (p=0.02). Conclusion: Combined HB vaccine and immunoglobulin had a better antibody response in the study as reported earlier. The carrier state was 1.44%.